Coupled SSPs-RCPs scenarios to project the future dynamic variations of water-soil-carbon-biodiversity services in Central Asia. (October 2021) - Li, Jiangyue; Chen, Xi; Kurban, Alishir; Van de Voorde, Tim; De Maeyer, Philippe; Zhang, Chi
Highlights: We proposed a coupling framework of SSPs/RCPs-FLUS-InVEST. Cropland degradation and urban and forestland expansion will occur in CA. Four ESs will exhibit different decreased trend across CA. Land-use policies should give priority to the trade-offs and synergies between ESs. Abstract: Global climate change and human activities are expected to have far-reaching implications for the associations between ecosystem services (ESs), especially in arid regions. Here, Central Asia (CA) was taken as a case study to describe the complex relationship among key ESs under the combined effects of future climate change and socioeconomic development. We propose a new framework that integrates the future land-use simulation (FLUS) model and integrated valuation of ESs and trade-offs (InVEST) model. A four-model ensemble mean from the Coupled Model Intercomparison Project 6 (CMIP6) was chosen to project future (2021–2100) variations in water yield (WY), soil conservation (SC), carbon storage (CS) and habitat quality (HQ). Spearman correlation was adopted to analyze the trade-offs and synergies between multiple ESs. Results showed that cropland degradation (−4.11% to −19.93%) and urban (+33.14% to +127.96%) and forestland (+5.31% to +25.52%) expansion will be the main forms of future land-use change in CA. Compared with the reference period (1995–2015), four ESs will exhibit different decreasing trends across CA under the three scenarios. We observed that the risk of soil erosion will increase in the mountainous areas of Kyrgyzstan and Tajikistan; cropland degradation and urban expansion would lead to a sharp reduction of CS and HQ in the Amu Darya Basin, Syr Darya Basin and southern Turkmenistan, especially in SSP245 scenario. We found that the weak pairwise correlations between HQ, SC and CS will be strengthened (R = 0.22–0.58; p < 0.05) in Kyrgyzstan and Tajikistan, whereas the significant positive correlation (R = 0.47–0.60; p < 0.01) between WY and SC will be weakened. An important information/recommendation provided by this study is that different management strategies should be designed in accordance with the major interactions among water, soil, carbon and biodiversity services.